2007
DOI: 10.1007/s10067-007-0717-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessments with SF 36 in different musculoskeletal diseases

Abstract: The aim of this study is to evaluate comparatively the life quality of patients with knee osteoarthritis (KO), shoulder impingement syndrome(SIS), fibromialgia(FM), or osteoporosis(OP) using SF 36 and establish the impact of these diseases on quality of life (QoL). A total of 193 patients with one of the above-mentioned different diagnoses completed SF 36 scale. The diseases were compared to each other with SF 36 subgroups scores. There were significant differences among patients with KO and SIS, SIS and FM wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 18 publications
3
28
0
3
Order By: Relevance
“…Sixteen studies that met all inclusion criteria were included in the final analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] with a total of 3131 men and women (1698 with vertebral fracture, and 1433 without vertebral fracture). Fourteen of these studies were cross-sectional [13-17, 19, 20, 22-28], one case-control [21], and one baseline data from an RCT [18].…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixteen studies that met all inclusion criteria were included in the final analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] with a total of 3131 men and women (1698 with vertebral fracture, and 1433 without vertebral fracture). Fourteen of these studies were cross-sectional [13-17, 19, 20, 22-28], one case-control [21], and one baseline data from an RCT [18].…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
“…Osteoporosis was defined as T score ≤ 2.5 SD, and lumbar BMD was measured in five studies [19][20][21][22]24], eight studies reported lumbar or/and hip BMD [13, 16-18, 23, 25, 27, 28], and in three studies the site of DXA scan was not mentioned [14,15,26]. Vertebral fractures were identified using Semi-quantitative (SQ) method in 11 studies [13, 16, 17, 21-25, 27, 28], quantitative morphometric (QM) method in two studies [14,19], the SQ, the binary semi quantitative (BSQ), and the QM in one study, the Japanese diagnostic criteria in one study [26], and in one study the method is not mentioned [15]. The number of participants with vertebral fracture in each study ranged from 9 [28] to 548 [17].…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
See 3 more Smart Citations